Citizen science in elementary classrooms: a tale of two teachers - Carrier, Sarah J.; Scharen, Danielle R.; Hayes, Meredith; Smith, P. Sean; Bruce, Anna; Craven, Laura (Frontiers in Education, 2024)
Introduction: Elementary teachers face many challenges when including reform-based science instruction in their classrooms, and some teachers have chosen to enhance their science instruction by introducing students to citizen science (CS) projects. When CS projects are incorporated in formal school settings, students have an opportunity to engage in real-world projects as they collect and make sense of data, yet relatively few CS projects offer substantial guidance for teachers seeking to implement the projects, placing a heavy burden on teacher learning.Methods: Framed in theory on teacher relationships with curricula, we prepared science standardsaligned educative support materials for two CS projects. We present convergent mixed methods research that examines two teachers' contrasting approaches to including school-based citizen science (SBCS) in their fifth-grade classrooms, each using support materials for one of the two CS projects. Both are veteran teachers at under-resourced Title 1 (an indicator of the high percentage of the students identified as economically disadvantaged) rural schools in the southeastern United States. We document the teachers' interpretations and use of SBCS materials for the CS projects with data from classroom observations, instructional logs, teacher interviews, and student focus groups.Results: One teacher adapted the materials to include scaffolding to position students for success in data collection and analysis. In contrast, the second teacher adapted the SBCS support materials to maintain a teacher-centered approach to instruction, identifying perceptions of students' limited abilities and limited instructional time as constraining factors. Discussion: We discuss the intersection of CS projects in formal education and opportunities for engaging students in authentic science data collection, analysis, and sense-making. The two teachers' stories identify the influences of school context and the need for teacher support to encourage elementary teachers' use of SBCS instruction to supplement their science instruction